Unveiling the molecular features, relevant immune and clinical characteristics of SIGLEC15 in thyroid cancer - Hou, Xiaofeng; Chen, Chao; Lan, Xiabin; He, Xiaodong (Frontiers in Immunology, 2022)
The groundbreaking research work about SIGLEC15 has raised it as a potential promising target in cancer immunotherapy. Unfortunately, the role of SIGLEC15 in thyroid carcinoma (THCA) remains obscure. Public and home multi-omics data were collected to investigate the role of SIGLEC15 in THCA in our study. SIGLEC15 was upregulated in THCA tumor tissue compared to nontumor tissue in both mRNA and protein levels; gene set enrichment analysis (GSEA) results showed that high SIGLEC15 mRNA expression was positively correlated to many immune pathways. Results of the examination of immunological landscape characteristics displayed high SIGLEC15 mRNA expression that mainly positively correlated with a large number of cancer immunity immunomodulators and pathways. In addition, upregulation of SIGLEC15 was positively correlated with an enhanced immune score, stromal score, and estimate score. However, higher SIGLEC15 mRNA also met high immune exhausted status. The majority of CpG methylation sites negatively correlated with SIGLEC15 mRNA expression. Analysis of clinical characteristics supported increased SIGLEC15 expression that was positively correlated with more extrathyroid extension and lymph node metastasis. We observed different single nucleotide variant (SNV) and copy number variation (CNV) patterns in high and low SIGLEC15 mRNA expression subgroups; some vital DNA damage repair deficiency scores addressed a negative correlation with SIGLEC15 mRNA expression. We also found that some commonly used chemotherapy drugs might be suitable for different SIGLEC15 mRNA expression subgroups. This study highlighted the vital role of SIGLEC15 in THCA. Targeting SIGLEC15 may offer a potential novel therapeutic opportunity for THCA patients. However, the detailed exact cellular mechanisms of SIGLEC15 in THCA still needed to be elucidated by further studies.